(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
The objective of this work is to develop a reflection on the concept of fifth estate based on the concept of fifth estate, proposed by Dutton (2009), which is presented as the manifestations of citizens in the digital environment in order to charge and supervise the media, here assumed as the fourth power, and the other powers. The methodologies used will be: bibliographic and documentary research (Gil, 2008), important for understanding the British scenario, and Analysis of Audiovisual Materiality (Coutinho, 2016; 2018), which enables the investigation of audiovisual content in its entirety and without decomposition. The preliminary results point to an appropriation of the fifth estate in the Brazilian context and we have developed as an intermediate theory (Braga, 2016; 2020) the concept of fifth estate, which despite having characteristics similar to the fifth estate, takes on new nuances and characteristics.